(untitled) (Bangladesh Journal of Botany, 2018)
For in vitro micropropagation, short day tropical varieties of onion ‘Agrifound Dark Red’, ‘Punjab Naroya’ and ‘PRO-6’ were exposed to different concentrations and combinations of growth hormones. Pre-sterilization of basal plate of onion in 0.5% solution of bavistin followed by treatment with 0.1% mercuric chloride for 10 min. produced the highest rate of survival of explants (47.9%). Survival was further enhanced to 53.17% with the addition of 750 ppm cefotaxime in MS medium. Varietal differences were observed for in vitro establishment, multiplication and root induction. Among various combinations of growth hormones, MS medium supplemented with 4.0 mg/l BAP + 0.5 mg/l NAA, 2 mg/l BAP and 0.5 mg/l NAA and half MS carrying 1.0 mg/l IBA + 0.5 mg/l NAA produced the highest in vitro establishment (53.07%), multiplication (64.46%) and rooting (66.37%) respectively, in ‘Agrifound Dark Red’.